Semi-standardized evaluation of extraprostatic extension and seminal vesicle invasion with [18F]PSMA-1007 PET/CT: a comparison to MRI using histopathology as reference - Erland Hvittfeldt; Fredrik Hedeer; Erik Thimansson; Kevin Sandeman; David Minarik; Jacob Ingvar; Anders Bjartell; Elin Trägårdh (EJNMMI Reports)
Abstract Background Positron emission tomography/computed tomography (PET/CT) with prostate specific membrane antigen ligands (PSMA) is established for use in primary staging of prostate cancer to screen for metastases. It has also shown promise in local tumor staging, including detection of extraprostatic extension (EPE) and seminal vesicle invasion (SVI). Previous studies have shown high heterogeneity in methods and results. Our aim was to compare [18F]PSMA-1007 PET/CT to magnetic resonance imaging (MRI) in evaluation of EPE and SVI, building on a previously described method for standardized evaluation. We retrospectively included 124 patients who had undergone MRI, PSMA PET/CT and prostatectomy. PSMA PET/CT images were evaluated by two nuclear medicine physicians. Using a standardized method, they measured length of capsular contact (LCC) and assessed EPE and SVI visually with the use of 5-point Likert scales. A radiologist evaluated MRI images using criteria based on Prostate Imaging–Reporting and Data System version and incorporating LCC measurement and Likert scales. We evaluated diagnostic performance with histopathology as reference, and the interrater reliability of the PET evaluations. Results The sensitivity and specificity for detecting EPE with the quantitative LCC method for PSMA PET/CT was 0.46/0.91, for the visual method 0.28/0.82 and for the combination of the two 0.54/0.76. AUC in ROC analysis for the LCC method was 0.70. For MRI the sensitivity and specificity were 0.80/0.64. For SVI, PET/CT and MRI had sensitivity and specificity of 0.14/1.0 and 0.50/0.92 respectively. The intraclass correlation coefficient for the PET LCC measurement was 0.68, the kappa values for the visual Likert scales for PET were 0.53 for EPE and 0.63 for SVI. Conclusions In this study, we attempted to standardize quantitative and qualitative PSMA PET/CT evaluation of EPE and SVI and compare the method with MRI. MRI had a higher sensitivity for EPE while PSMA had a higher specificity. For SVI, both methods had high specificity. The interrater reliability for the PSMA PET/CT evaluations was moderate to substantial.